Urban Telemedicine: The Applicability of Teleburns in the Rehabilitative Phase. Issue 1 (January 2017) - Liu, Yuk Ming; Mathews, Katie; Vardanian, Andrew; Bozkurt, Taylan; Schneider, Jeffrey C.; Hefner, Jaye; Schulz, John T.; Fagan, Shawn P.; Goverman, Jeremy
Abstract : Telemedicine has been successfully used in many areas of medicine, including triage and evaluation of the acute burn patient. The utility of telemedicine during the rehabilitative phase of burn care has yet to be evaluated; therefore, we expanded our telemedicine program to link our burn center with a rehabilitation facility. The goal of this project was to demonstrate cost–effective improvements in the transition and quality of care. A retrospective review was performed on all patients enrolled in our telemedicine/rehabilitation program between March 2013 and March 2014. Data collected included total number of encounters, visits, type of visit, physician time, and readmissions. Transportation costs were based on local ambulance rates between the two facilities. The impact of telemedicine was evaluated with respect to the time saved for the physician, burn center, and burn clinic, as well as rehabilitative days saved. A patient satisfaction survey was also administered. A total of 29 patients participated in 73 virtual visits through the telemedicine project. Virtual visits included new consults, preoperative evaluations, and postoperative follow-ups. A total of 146 ambulance transports were averted during the study period, totaling $101, 110. Virtual visits saved 6.8 outpatient burn clinic days, or 73 clinic appointments of 30-min duration. The ability to perform more outpatient surgery resulted in 80 inpatient bed days saved at the burn hospital. The rehabilitation hospital saved an average of 2 to 3 patient days secondary to unnecessary travel. Satisfaction surveys demonstrated patient satisfaction with the encounters, primarily related to time saved. The decrease in travel time for the patient from the rehabilitation hospital to outpatient burn clinic improved adherence to the rehabilitation care plan and resulted in increased throughput at the rehabilitation facility. Videoconferencing between a burn center and rehabilitation hospital streamlined patient care and reduced health care costs, while maintaining quality of care and patient satisfaction. This program has improved inpatient burn rehabilitation by maximizing time spent in therapy and avoiding unnecessary patient travel to offsite appointments.